2022
DOI: 10.3390/catal12030290
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Stimulated Adsorption of Cr(VI) from Aqueous Solution by Groundnut Shell Activated Carbon@Al Embedded Material

Abstract: In this study, a low-cost bioadsorbent aluminum metal blended with groundnut shell activated carbon material (Al-GNSC) was used for Cr(VI) adsorption from aqueous solutions. Al-GNSC was prepared and characterized using Fourier transform infrared spectrometer (FT-IR), scanning electron microscopic (SEM) and X-ray diffraction (XRD) to determine its surface morphology. Batch studies were performed and the optimum conditions for maximum Cr(VI) removal (of 94.2%) were found at pH 4.0, initial concentration 100 mg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The experimentally obtained Cr 6+ sorption isotherm data are fitted with the Langmuir model which yielded R 2 ∼ 0.98 (Figure D). The Langmuir constant, b , was obtained as 0.005(2) L/mg and is comparable to other Cr 6+ adsorbents …”
Section: Results and Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The experimentally obtained Cr 6+ sorption isotherm data are fitted with the Langmuir model which yielded R 2 ∼ 0.98 (Figure D). The Langmuir constant, b , was obtained as 0.005(2) L/mg and is comparable to other Cr 6+ adsorbents …”
Section: Results and Discussionsupporting
confidence: 69%
“…The Langmuir constant, b, was obtained as 0.005(2) L/ mg and is comparable to other Cr 6+ adsorbents. 53 To determine the effectiveness of LDH−Mo 3 S 13 for Cr 6+ removal in the presence of highly competitive ions in purified and naturally contaminated water, we investigated Cr 6+ removal efficiency from tap water and Mississippi River water (collected from Vidalia, Louisiana) by spiking them with 1000 ppb of Cr 6+ (CrO 4 2− ) (Figures 2E and 2F, Table S7). This study showed that despite the presence of numerous ions, such as Ca 2+ , Mg 2+ , Na + , K + , HCO 3 − , SO 4 2− , and Cl − , and other organic or inorganic constituents, LDH−Mo 3 S 13 can remove ≥99.6% of Cr 6+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, the Hg(II) and Cr(VI) adsorption over CNTs–PLA–Pd occurred through monolayer molecular covering and chemisorption together [ 74 ]. The maximum adsorption capacity (q m ) of CNTs–PLA–Pd estimated for Hg(II) and Cr(VI) adsorption was compared to the reported values for different adsorbents and presented in Table 3 and Table 4 , respectively [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]. The stability of CNTs–PLA–Pd was estimated by recovering and applying it in three subsequent cycles of adsorption of Hg(II).…”
Section: Resultsmentioning
confidence: 99%
“…Where, Ci and Cf (mg/L) are the initial and the equilibrium concentration, V(L) is volume of the used solution, and the amount of dry adsorbent used is m (g) (Vaddi et al 2022).…”
Section: Effect Of Phmentioning
confidence: 99%